Synthesis, Complexation, and Biological Activity Studies of 4-Aminomethyl-7,8-dihydroxy Coumarines and Their Crown Ether Derivatives - (:unkn) unknown (WILEY, 2010)
The article focuses synthesis of novel 4-aminomethyl-7,8-dihydroxy coumarins and their crown ether derivatives. The purified novel coumarins and their crown ether derivatives were identified by H-1 NMR, C-13 NMR, mass spectrometry and elemental analysis. The 1:1 binding constants of Ca2+, Mg2+, Fe2+, Zn2+, Ni2+, Cd2+, Co2+, and Mn2+ ions at 25 degrees C +/- 0.1 with the 4-aminomethyl-7,8-dihydroxy coumarins and their crown ether derivatives estimated using extraction procedure with Inductively Coupled Plasma-Atomic Emission Spectroscopy in dichloromethane/water membrane systems. Synthesized compounds were investigated for complexation and biological activity properties. Best results in biological activity studies were observed for antioxidant activity.
Keywords: EXCITED-STATE PROPERTIES; SOLVENT-EXTRACTION; (COUMARIN-4-YL)METHYL DERIVATIVES; FUNDAMENTAL EQUILIBRIA; DEACTIVATION BEHAVIOR; CYCLIC POLYETHERS; METAL PICRATES; ION-PAIR; 18-CROWN-6; PHOTOCLEAVAGE